Occupational Prestige from the Nurses Point of View - Hossein Sadeghnezhad; Majid Ghanei Allhosseini (Guilan University of Medical Sciences, 2020)
Introduction: Low nursing occupational prestige is the major challenge in nursing as a job in Iran. A high occupational prestige naturally causes self-esteem in the individuals and succeeding mainly with a job satisfaction. Objective: Considering the importance and necessity of the nursing occupational prestige, this study aimed to evaluate occupational prestige and its relationship with some demographic characteristics of the nurses. Materials and Methods: This cross-sectional analytical study was carried out on all nurses occupied in the hospitals of Kashmar City in 2018, with 230 persons. Data were collected using a validated and reliable Nursing Occupational Prestige Questionnaire. Scores ranged 16-64. Scores 27-38 indicate low occupational prestige, 39-50 shows moderate occupational prestige, and 51-64 shows high occupational prestige. Data were analyzed using descriptive statistics and inferential statistics tests (Spearman correlation coefficient, Kruskal-Wallis, and Mann-Whitney U). Results: The mean score of occupational prestige of the subjects was 44.09±6.18. Results showed that 21.3% (n=47) of participants had low occupational prestige, 65.5% (n=144) had moderate occupational prestige and 13.2% (n=29) had high occupational prestige. There was a significant relationship between occupational prestige and level of education (P=0.01), university of education (P=0.01), and nurses' organizational position (P=0.05). Conclusion: Most nurses had moderate occupational prestige. Nursing managers are recommended to develop a comprehensive plan to improve the occupational prestige of nurses working in hospitals. Since there is a significant relationship between the level of nursing education and the perception of occupational prestige, it seems that providing the appropriate conditions to enhance the level of nursing education can be effective in promoting the occupational prestige they feel they deserve.